Role of oxygen flow rate on the structure and stoichiometry of cobalt oxide films deposited by reactive sputtering - Neto, Nilton Francelosi A. [UNESP]; Stegemann, Cristiane; Affonço, Lucas J. [UNESP]; Leite, Douglas M. G.; Da Silva, José H. D. [UNESP] (American Vacuum Society, 2022)
The influence of the oxygen gas supply on the stoichiometry, structure, and orientation texture of polycrystalline cobalt oxide films was investigated in this study. The films were grown by direct current reactive magnetron sputtering using a metallic Co target and different O2 inlet flow rates (0.5-5.0 SCCM). The deposition power (80 W), the argon gas flow (40 SCCM), and the total working pressure (0.67 Pa) were kept constant during depositions. The results evidence a strong influence of the oxygen flow over the film's stoichiometry and structure, where low oxygen flows (<2.0 SCCM) favor the formation of the rock salt CoO phase while higher oxygen flows (>2.5 SCCM) favor the spinel Co3O4 phase formation. The coexistence of monoxide and tetraoxide phases is only observed for the 2.5 SCCM oxygen flow condition. Strain effects related to the oxygen partial pressure are also observed and discussed. Computer simulations of the reactive sputtering growth supported the analysis of the film properties and its correlation to the oxygen partial pressure.